Evaluation of Growth Intensity in Suffolk and Charollais Sheep - Janoš, Tomáš; Filipčík, Radek; Hošek, Martin (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The aim of the study was to evaluate the influence of breed (Suffolk, Charollais), sex (ram, ewes) and litter size (singles, twins, triplets) on the growth ability of lambs from birth to 300 days of age. Insignificantly higher (p > 0.05) birth weight (4.47 ± 1.07 kg), weight in 30 days (13,87 ± 3.28 kg), 100 days (36.51 ± 5.80 kg) and 300 days (79.00 ± 13.64 kg) was found in the lambs of the Suffolk breed. Higher birth weight was also associated with larger body dimensions in the Suffolk breed (height at withers 42.43 cm, diagonal length of body 43.60 cm). In 100 days, the lambs of Charollais were slightly bigger, in 300 days the height at withers and the diagonal length of body were nearly the same in both breeds. Higher growth intensity was recorded in rams (DG0−300: Ram = 239.87 g. day−1, Ewe = 221.67 g. day−1). With regard to the litter size, higher growth intensity was found in singles (234.77 g. day-1) when compared to lambs from twins (226.10 g. day−1) or triplets (225.63 g. day−1).